Sons of Saviors : The Red Jews in Yiddish Culture - Voß, Rebekka (Jewish culture and contexts., 2023)
Envisioned as a tribe of ruddy-faced, redheaded, red-bearded Jewish warriors, bedecked in red attire who purportedly resided in isolation at the fringes of the known world, the Red Jews are a legendary people who populated a shared Jewish-Christian imagination. But in fact the red variant of the Ten Lost Tribes of Israel is a singular invention of late medieval vernacular culture in Germany. This idiosyncratic figure, together with the peculiar term "Red Jews," existed solely in German and Yiddish, the German-Jewish vernacular. These two language communities assessed the Red Jews differently and contested their significance, which is to say, they viewed them in different shades of red. The voyage of the Red Jews through the Jewish and Christian imagination, from their medieval Christian nascence, through early modern Old Yiddish literature, to modern Yiddish culture in Eastern Europe, Palestine, and America, is the story of this book.By studying this vernacular icon, Rebekka Voß contributes to our understanding of the formation of minority awareness and the construction of Ashkenazic Jewish identity through visual cultural encounters. She also spotlights the vitality of vernacular culture by demonstrating how the premodern motif of the Red Jews informed modern Yiddish literature, and how the stereotype of Jewish red hair found its way into Jewish social critiques, political thought, and arts through the present day.Sons of Saviors is a story about power: the Yiddish reappropriation of the Red Jews subverted the Christian color symbolism by adjusting the focus on redness from a negative stereotype into a proud badge of self-assertion. The book also includes in an appendix the full text of a significant Yiddish tale featuring the Red Jew, translated by the author.